The Impact of Service Quality and Food Quality on Customer Satisfaction and Customer Retention - Ni Ketut Karwini; Ni Wayan Ana Rahita Handayani; Ida Ayu Trisna Wijayanthi (Malaqbi Publisher, 2026)
This study investigates the impact of service quality and food quality on customer satisfaction and customer retention in the restaurant industry. Drawing on a quantitative research design, data were collected from 215 restaurant customers using a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among the constructs. The findings reveal that service quality and food quality significantly and positively influence customer satisfaction, with food quality demonstrating a stronger effect. Customer satisfaction was found to have a substantial positive impact on customer retention, confirming its central role in fostering long-term customer relationships. Additionally, the results indicate that customer satisfaction partially mediates the relationships between service quality and retention, as well as between food quality and retention. The model explains a considerable proportion of variance in both customer satisfaction and customer retention, suggesting strong predictive power. These findings highlight the strategic importance of delivering consistent food excellence and superior service performance to enhance customer satisfaction and ensure sustainable customer retention. The study contributes to hospitality and service marketing literature by providing an integrated empirical framework linking quality dimensions, satisfaction, and retention within the restaurant context.